(untitled) (Damascus University Journal of arts and humanities sciences, 2026)
The child’s use of the Internet has a significant impact on the child’s socialization process, and this impact may be positive and effective in the child’s development and social upbringing, due to the programs offered by some Internet sites that instill the desired moral, social, cognitive, and cultural values ​​in society, and among the positive effects as well. Developing the child’s sense of responsibility, as well as familiarizing him with the socially necessary concepts and standards for the social adaptation process. However, the child’s use of the Internet may have negative effects on the child’s socialization process, such as the child acquiring customs that are foreign to the customs of his society, such as imitating other societies in dress or language, or Listening to songs that are strange to his community, and the Internet may also negatively affect the child’s interaction with other children. Because of his preoccupation with using the Internet, the child may also be exposed to a number of negative values ​​via the Internet such as: ridicule, insults, and exploitation, as well as mental, physical, and health fatigue for the child, and other effects that play a negative role in the child’s socialization process.